Applying the ESC 2016, the H2FPEF, and the HFA-PEFF diagnostic algorithms for heart failure with preserved ejection fraction to the general population – a comparative approach. (14th October 2021) - Nikorowitsch, J; Bei Der Kellen, R; Kirchhof, P; Magnussen, C; Schnabel, R; Blankenberg, S; Wenzel, J.P; ,
Abstract: Background: Heart failure with preserved ejection fraction (HFpEF) is common in patients presenting with dyspnoea. Nevertheless, diagnosing HFpEF remains challenging. Recently, different algorithms were developed to predict the likelihood of HFpEF. Purpose: Our objective was to provide an in-depth comparison of the ESC 2016 algorithm, the H2FPEF- and the HFA-PEFF algorithm for diagnosing and characterising HFpEF in the general population. Methods: The study included 5, 613 participants of the population-based H. City Health Study (HCHS), aged 62±8.7 years (51.1% women), that were enrolled between 2016 and 2019. Exclusion criteria were other common causes of dyspnea. We calculated the prevalence and compared characteristics of HFpEF according to the different diagnostic algorithms applying the ESC 2016 heart failure guidelines and the cut-off values suggested by the authors of the HFA-PEFF and H2FPEF score for defining HFpEF. Results: Unexplained dyspnea was present in 407 (7.3%) subjects. In those, the estimated prevalence of HFpEF was 20.4% (ESC 2016), 12.3% (H2FPEF), and 7.6% (HFA-PEFF). The majority of subjects was classified as HFpEF not excludable according to the HFA-PEFF (57.7%) and the H2FPEF (59.2%) score. For all algorithms, subjects diagnosed with HFpEF showed elevated age and body mass index as well as a higher prevalence of atrial fibrillation, diabetes, and arterial hypertension compared to those without HFpEF or HFpEF not excludable. The distribution of those comorbidities and risk factors varied between the differently diagnosed HFpEF groups with the highest burden in the HFpEF group defined by the H2FPEF score. The overlap of subjects diagnosed with HFpEF according to the different algorithms was very limited. Conclusion: Unexplained dyspnoea is common in the middle-aged general population. The ESC 2016 algorithm, the H2FPEF-, and the HFA-PEFF score detect different, discordant sub-populations of probands with breathlessness. Further classification of the HFpEF syndrome is desirable. Funding Acknowledgement: Type of funding sources: Public grant(s) – EU funding. Main funding source(s): Innovative medicine initiative